The role of solvent-accessible leu-208 of cold-active Pseudomonas fluorescens strain AMS8 lipase in interfacial activation, substrate accessibility and low-molecular weight esterification in the presence of toluene - Yaacob, Norhayati; Kamarudin, Nor Hafizah Ahmad; Thean, Adam Chor Leow; Salleh, Abu Bakar; Rahman, Raja Noor Zaliha Raja Abd; Ali, Mohd. Shukuri Mohamad (MDPI, 2017)
The alkaline cold-active lipase from Pseudomonas fluorescens AMS8 undergoes major structural changes when reacted with hydrophobic organic solvents. In toluene, the AMS8 lipase catalytic region is exposed by the moving hydrophobic lid 2 (Glu-148 to Gly-167). Solvent-accessible surface area analysis revealed that Leu-208, which is located next to the nucleophilic Ser-207 has a focal function in influencing substrate accessibility and flexibility of the catalytic pocket. Based on molecular dynamic simulations, it was found that Leu-208 strongly facilitates the lid 2 opening via its side-chain. The KM and Kcat/KM of L208A mutant were substrate dependent as it preferred a smaller-chain ester (pNP-caprylate) as compared to medium (pNP-laurate) or long-chain (pNP-palmitate) esters. In esterification of ethyl hexanoate, L208A promotes a higher ester conversion rate at 20 °C but not at 30 °C, as a 27% decline was observed. Interestingly, the wild-type (WT) lipase's conversion rate was found to increase with a higher temperature. WT lipase AMS8 esterification was higher in toluene as compared to L208A. Hence, the results showed that Leu-208 of AMS8 lipase plays an important role in steering a broad range of substrates into its active site region by regulating the flexibility of this region. Leu-208 is therefore predicted to be crucial for its role in interfacial activation and catalysis in toluene.